2008
DOI: 10.1108/17561370910915384
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of dairy farming and poverty reduction in Inner Mongolia, China

Abstract: PurposeThe purposes of this paper are to examine the actual conditions of the problems of poverty in rural areas in Inner Mongolia, to clarify the problems involved in the measure to fight poverty through promotion of dairy farming and to propose policies for future measures to fight poverty.Design/methodology/approachBoth quantitative and qualitative analyses are employed, such as the estimation of production functions of agriculture in Inner Mongolia over the period 1998‐2004, the interview analysis and ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…However, the study has tried to cover most of the highest quality literature available in the WoS database published in the past 50 years. (Christiaensen & Todo, 2013Ferreira et al, 2010;Cazzuffi et al, 2017;Mellor & Malik, 2017;Kimura & Cheng, 2017;Christiaensen & Luc, 2017;Hu et al, 2016;Long et al 2016;Si et al, 2015;Tobias et al, 2013;Sigalla & Carney, 2012;Heo & Nguyen, 2009;Jack, 2006;Si et al, 2019;Chen et al, 2019;Wu & Si, 2018;Keovilignavong & Suhardiman, 2018;Kolade, 2018) 2 Poverty alleviation through the adoption of agricultural technology (Ferraro et al, 2011;Christiaensen et al, 2011;Mendola, 2007;Jayne et al, 2003;Thirtle et al, 2003;Montalvo & Ravallion, 2010;Badibanga & Ulimwengu, 2019;Alene et al, 2018;Imai et al, 2017;Van & Maertens, 2017;Mbuyisa & Leonard, 2017;Shrestha et al, 2016;Herman, 2016;Abro et al, 2014;Choudhury et al, 2014;Devkota & Upadhyay, 2013;Dorosh & Mellor, 2013;Asfaw et al, 2012;Dillon, 2011;Mkwambisi et al, 2011;de Janvry & Sadoulet, 2010;Dagula, 2009;…”
Section: Discussionmentioning
confidence: 99%
“…However, the study has tried to cover most of the highest quality literature available in the WoS database published in the past 50 years. (Christiaensen & Todo, 2013Ferreira et al, 2010;Cazzuffi et al, 2017;Mellor & Malik, 2017;Kimura & Cheng, 2017;Christiaensen & Luc, 2017;Hu et al, 2016;Long et al 2016;Si et al, 2015;Tobias et al, 2013;Sigalla & Carney, 2012;Heo & Nguyen, 2009;Jack, 2006;Si et al, 2019;Chen et al, 2019;Wu & Si, 2018;Keovilignavong & Suhardiman, 2018;Kolade, 2018) 2 Poverty alleviation through the adoption of agricultural technology (Ferraro et al, 2011;Christiaensen et al, 2011;Mendola, 2007;Jayne et al, 2003;Thirtle et al, 2003;Montalvo & Ravallion, 2010;Badibanga & Ulimwengu, 2019;Alene et al, 2018;Imai et al, 2017;Van & Maertens, 2017;Mbuyisa & Leonard, 2017;Shrestha et al, 2016;Herman, 2016;Abro et al, 2014;Choudhury et al, 2014;Devkota & Upadhyay, 2013;Dorosh & Mellor, 2013;Asfaw et al, 2012;Dillon, 2011;Mkwambisi et al, 2011;de Janvry & Sadoulet, 2010;Dagula, 2009;…”
Section: Discussionmentioning
confidence: 99%
“…Studies have specifically identified dairy farming as a critical source of livelihoods and nutritional security in a number of different lower-income communities, nations, and regions, such as parts of Sub-Saharan Africa (Chagunda et al, 2016;Kidoido & Korir, 2015;Rao et al, 2016;Ulicky et al, 2013); Bangladesh (Rahman, 2007); the Gaza Strip (Rossignoli et al, 2015); Inner Mongolia, China (Kiminami, 2009); Nepal (Singh & Maharjan, 2005); and India (Singh & Datta, 2013). Furthermore, an FAO review found that across household-level randomized control trials and observational studies with a comparison group, dairy cow ownership and/or the improvement of dairy cow production had a consistent positive impact on indicators of household welfare around the world (FAO et al, 2018).…”
Section: Lower-income Nations and Regionsmentioning
confidence: 99%
“…Therefore, a perspective on the "food system", which covers problems involving foodstuffs such as the flow of food and the environment surrounding it, is needed (Kiminami 2009). Generally, the food we eat today has to travel a long distance "from farm to table".…”
Section: The Perspective On the Food Systemmentioning
confidence: 99%
“…Furthermore, the change in network centeredness is summarized in Table 1.8. Furthermore, Source: Kiminami (2009), Kiminami and Furuzawa (2014) Notes: Calculated from Asian International Input-Output Table, editions for 1985, 1990, 1995, 2000, and 2005, Institute of Developing Economies using the Simple Network Analysis Tool (software) the driving forces of the transactions which strengthened the presence of China's food system in the region are considered to be the early harvest for the agricultural sector in the FTA with ASEAN in 2003 and China's accession to the WTO. However, the centrality of China's food manufacturing industry (AC008) grew from 2000 to 2005.…”
Section: Food and Agricultural Exports From Korea To Japan And Chinamentioning
confidence: 99%
See 1 more Smart Citation